2012
DOI: 10.1002/iub.1086
|View full text |Cite
|
Sign up to set email alerts
|

Potential prognostic biomarker CD73 regulates epidermal growth factor receptor expression in human breast cancer

Abstract: SummaryCD73, an ecto-enzyme overexpressed in breast-cancer cells, catalyzes the dephosphorylation of adenosine monophosphates into adenosine. Anti-CD73 slows breast cancer growth and its spread both in vivo and in vitro. In this study, we investigated the relation of CD73 to epidermal growth factor receptor (EGFR) expression using tissue array and breast cancer cell lines. We found that CD73 expression correlated positively to EGFR expression in vivo (n 5 80, r 5 0.425, P \ 0.01) and in vitro. EGFR expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 37 publications
7
46
0
Order By: Relevance
“…Consistent with this idea, it has been reported that CD73 is overexpressed in different types of tumors and cell lines. Interestingly, in breast cancer cells, CD73 overexpression has been associated with invasiveness and drug resistance [32],[33],[34]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, it has been reported that CD73 is overexpressed in different types of tumors and cell lines. Interestingly, in breast cancer cells, CD73 overexpression has been associated with invasiveness and drug resistance [32],[33],[34]. …”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, downregulation of EGFR by siRNA resulted in inhibition of migration and invasion activities in pcDNA-NT5E transfected T-47D cells. In another study, researchers found that CD73 expression correlated positively to EGFR expression in MB-MDA-231 cells, and EGFR expression could be decreased by suppressing CD73 expression with siRNA [38]. These observations suggested that CD73 promoted tumor cell migration and invasion via regulating EGFR expression.…”
Section: Cd73 and Tumor Metastasismentioning
confidence: 99%
“…Thus, the promotive effect of CD73 on cancer cells proliferation in vitro may via other molecule which independent with adenosine, such as EGFR, which is a key molecule involved in cell growth. Recently, Zhi et al have found the regulative effect of CD73 on EGFR expression and phosphorylation in human breast cancer [38]. …”
Section: Cd73 and Tumor Growthmentioning
confidence: 99%
“…Supernat et al showed that elevated CD73 expression in breast cancer can predict a good prognosis of the disease [26]. In addition, Zhi et al suggested that CD73 may be used as a potential prognostic & therapeutic biomarker for breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%